Long Non-Coding RNA Expression during Aging in the Human Subependymal Zone - Barry, Guy; Guennewig, Boris; Fung, Samantha; Kaczorowski, Dominik; Weickert, Cynthia Shannon (Frontiers in Neurology, 2015)
The human subependymal zone (SEZ) is debatably a source of newly born neurons throughout life and neurogenesis is a multi-step process requiring distinct transcripts during cell proliferation and early neuronal maturation, along with orchestrated changes in gene expression during cell state/fate transitions. Furthermore, it is becoming increasingly clear that the majority of our genome that results in production of non-protein coding RNAs plays vital roles in the evolution, development, adaptation and region-specific function of the human brain. We predicted that some transcripts expressed in the SEZ may be unique to this specialized brain region, and that a comprehensive transcriptomic analysis of this region would aid in defining expression changes during neuronal birth and growth in adult humans. Here, we used deep RNA sequencing of human SEZ tissue during adulthood and aging to characterize the transcriptional landscape with a particular emphasis on long non-coding RNAs (lncRNAs). The data shows predicted age-related changes in mRNAs encoding proliferation, progenitor and inflammatory proteins as well as a unique subset of lncRNAs that are highly expressed in the human SEZ, many of which have unknown functions. Our results suggest the existence of robust proliferative and neuronal differentiation potential in the adult human SEZ and lay the foundation for understanding the involvement of lncRNAs in postnatal neurogenesis and potentially associated neurodevelopmental diseases that emerge after birth.